Value-relevance of nonfinancial information: The wireless communications industry - Amir, Eli; Lev, Baruch (Journal of Accounting and Economics, 1996)
We examine the value-relevance to investors of financial (accounting) and nonfinancial information of independent cellular companies and find that, on a stand-alone basis, financial information (earnings, book values, and cash flows) are largely irrelevant for security valuation. Nonfinancial indicators, such as POPS (a growth proxy) and Market Penetration (an operating performance measure), are highly value-relevant. However, combined with nonfinancial information, earnings do contribute to the explanation of prices. The complementarity between financial and nonfinancial data is highlighted in this study.